SISTEM INFORMASI ENTERPRISE PADA BALI ETAWA FARM - Pande Made Widiarjaya WD; I Gede Juliana Eka Putra; I Nyoman Yudi Anggara Wijaya (Journal of Applied Management and Accounting Science, 2020)
Information technology has developed in various fields of life. Along with these developments, technology also plays a very important role in agriculture and animal husbandry. However, the Bali Etawa Farm company has not utilized information technology so that in carrying out its business processes there are obstacles. One of the obstacles facing Bali Etawa Farm today is that the existing processes are not yet integrated, both in terms of production, sales and warehouse processes. With these problems, it is necessary to create an Enterprise Information System to integrate all processes in Bali Etawa Farm. The research method used in this research is the waterfall method which is also called the classic life cycle and data collection is interviews, observation and documentation at Bali Etawa Farm. Based on the results of data collection, the constraints and flow of business processes that exist at Bali Etawa Farm are identified. From these results, a system design, database design and interface design are made, from these designs then poured into the coding to make the system, after the system is completed, the system will be tested. The results of system testing are as expected so that the enterprise information system has been successfully created.